(untitled) (JOURNAL OF ADVANCES IN CHEMISTRY, 2015)
The omega polynomial Î©(G,x), for counting qoc strips in molecular graph G was defined by Diudea as Â with m(G,c), being the number of qoc strips of length c. The Theta polynomial Î˜(G,x) and the Theta index Î˜(G) of a molecular graph G were defined as Î˜(G,x)=Â and Î˜(G)=, respectively. In this paper, we compute the Theta polynomial Î˜(G,x) and the Theta index Î˜(G) of molecular graph Polycyclic Aromatic Hydrocarbons PAHk, for all positive integer number k.Â